The Determinants of Cryptocurrency Adoption: An Integrated Framework for the UAE - NICOLAS, SALAM IBRAHIM EL KHOURI (2025)
This study investigates the factors influencing cryptocurrency adoption intentions among consumers in the United Arab Emirates (UAE), a country positioning itself as a global blockchain and digital asset hub. Despite policy-driven advancements such as the Emirates Blockchain Strategy and the establishment of regulatory bodies such as Virtual Assets Regulatory Authority (VARA), cryptocurrency adoption among UAE residents remains limited. To address this gap, the research integrates the Uncertainty Framework, Perceived Risk Theory, and UTAUT2 to develop a holistic model examining how uncertainty, perceived risk, and technology acceptance shape consumer behaviour. The study adopts a quantitative, cross-sectional research design, employing a structured online questionnaire distributed to a sample of 450 UAE residents. Using Partial Least Squares Structural Equation Modelling (PLS-SEM) via WarpPLS 8.0, the analysis evaluates the measurement and structural models for reliability, validity, and predictive power. The findings reveal that perceived information asymmetry, technological uncertainty, regulatory ambiguity, and the intangibility of cryptocurrency services significantly influence perceived risk, which in turn affects the adoption intentions. Technological constructs from the UTAUT2, such as performance expectancy, effort expectancy, social influence, and trust, also emerge as critical factors shaping the adoption behaviour. This study contributes theoretically by extending the UTAUT2 with the risk and uncertainty constructs, and offers practical implications for regulators, developers, and marketers seeking to increase consumer engagement with cryptocurrencies in high-risk, innovation-driven environments like the UAE. The results underscore the importance of regulatory clarity, consumer education, and trust-building initiatives in bridging the gap between national blockchain ambitions and individual-level adoption.